2017
DOI: 10.1155/2017/5627062
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Preincision Ketamine on Postspinal Caesarean Delivery in Uganda’s Tertiary Hospital: A Randomized Clinical Trial

Abstract: Background. Good postoperative analgesic management improves maternal satisfaction and care of the neonate. Postoperative pain management is a challenge in Mulago Hospital, yet ketamine is accessible and has proven benefit. We determined ketamine's postoperative analgesic effects. Materials and Methods. We did an RCT among consenting parturients that were randomized to receive either intravenous ketamine (0.25 mg/kg) or placebo after spinal anesthetic. Pain was assessed every 30 mins up to 24 hours postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
3
6
1
Order By: Relevance
“…In Contrast to our study finding, study conducted in Uganda, 2017 showed diclofenac consumption was significantly lower in ketamine 75 (75–150) than control group 150 (75–150) in mg, but, total tramadol consumption was not significant [ 33 ]. This difference may due to pain control protocol difference, study design and sample size.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In Contrast to our study finding, study conducted in Uganda, 2017 showed diclofenac consumption was significantly lower in ketamine 75 (75–150) than control group 150 (75–150) in mg, but, total tramadol consumption was not significant [ 33 ]. This difference may due to pain control protocol difference, study design and sample size.…”
Section: Discussioncontrasting
confidence: 96%
“…This may increase satisfaction level of parturients, decrease post operative analgesia consumptions as request time elapsed and avoid side effect of multiple drug consumption in immediate post operative period. In line with our result, study done in Uganda, 2017 showed that median (range) time (in minutes) to first analgesia request was Significantly longer in the ketamine group [210 (90–270)] than control group [180 (90–360)] [ 33 ]. Similarly, RCT done in Nigeria, 2012 match with our study result that showed first analgesia request time was significantly higher in ketamine group(209 ± 14.7min) than control group (164 ± 14.1) [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…5 Based on its effective bronchodilating respiratory properties and stable hemodynamics, ketamine use has been reported in patients with brain injury, resulting in increased clinical use. 6 Moreover, the administration of ketamine as an anesthetic has branched for extraperitoneal procedures, cardiac catheterization, orthopedics, and skin grafting, as well as otolaryngology and optical procedures. 7 Lidocaine, firstly synthesized by the Swedish chemist Lofgren, has been used extensively, such as for pain management, clinical anesthesia, nervous system diseases, arrhythmia, treatment of respiratory diseases, and gastrointestinal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine is acknowledged among the oldest hypnotic agents for anesthesia due to its analgesic properties and minimal suppressive effects on respiration . Based on its effective bronchodilating respiratory properties and stable hemodynamics, ketamine use has been reported in patients with brain injury, resulting in increased clinical use . Moreover, the administration of ketamine as an anesthetic has branched for extraperitoneal procedures, cardiac catheterization, orthopedics, and skin grafting, as well as otolaryngology and optical procedures .…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine is an antagonist of the N-Methyl-D-Aspartate (NMDA) receptor which is often used as an anesthetic agent. NMDA receptor antagonists can provide an analgesic effect by desensitizing NMDA receptors, therefore inhibiting pain transmission in the central nervous system (7). Greater attention should be paid to this drug because it has been proven to be effective in relieving pain and is relatively available in remote areas (8).…”
Section: Introductionmentioning
confidence: 99%